Implementasi Metode Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Untuk Seleksi Calon Petugas Sensus Di Badan Pusat Statistik Seluma - Deko Aribowo; Yupianti Yupianti; Jhoanne Fredricka (Jurnal Media Infotama, 2024)
Central Bureau of Statistics is an institution tasked with providing quality statistical data through statistical activities that are integrated and have national and international standards. The purpose of this research is to produce a decision support system application for selecting prospective census officers at Central Bureau of Statistics of Seluma using Simple Additive Weighting (SAW) method. SAW is one of the methods used to solve problems. A decision Support System for the selection of prospective census officers at Central Bureau of Statistics of Seluma was created using PHP Programming Language and MySQL Database. This application can accommodate data on prospective census officers who will be assessed. This application can be used to facilitate the selection of prospective census officers at Central Bureau of Statistics of Seluma by applying SAW method which can rank the assessment results.